Malaysia network transit route adviser system - Mohd Syafiq, Bachok (2010)
Malaysia has been developed from one stage to another stage. By looking at the transportation in Malaysia, there are about too many types of transport that are commonly used either privàté or public_ s- uCh as Car and bus. One Of the frãñjóft which now days got attention from the public is transit such as KTM Commuter, Express Rail Link (ERL), I<L Monorail, Putra LRT and STAR -LRT. Mos± people like to use this type of transport because to avoid from traffic congestion on the road or to choose the easiest method to move from one destination to another. Nevertheless, these transit also facing with a lot of problems including the customer satisfaction and delay of train. Anyhow, the customer always faces difficulty to krnd the shortest route. Failed to do so the cost will be increased according to the route chosen and the time is not accurate. This is because there are too many option of route to go to each destination. This problem comes when users need to change from one train to another train to reach the destination. Until now Malaysia-has five type of transit that is often used. Malaysian Network Transit Route Advisor (MANTRA) is a web based system that especially developed to guide the people when using the Malaysian Transit. MANTRA has two main functions. The first is to estimate the lowest cost base on time travelling from one station to another and the second function is estimate the lowest cost base on the ticket price. MANTRA using Dijkstra's Algorithm to realize these functions. frIANTRA 98% successfully to advice the tourist goes to the destination using Malaysia Transit.